2020
DOI: 10.3389/fpsyg.2020.01849
|View full text |Cite|
|
Sign up to set email alerts
|

Parental Attunement, Insightfulness, and Acceptance of Child Diagnosis in Parents of Children With Autism: Clinical Implications

Abstract: Early parent-child relationships are an important factor influencing many domains of child development, even in the presence of autism. In this study, we investigated the associations between parent-child attunement during play, parental insightfulness, and parental acceptance of their child's diagnosis of an autism spectrum disorder. A sample of 50 parents (26 mothers and 24 fathers) of 26 children aged between 24 and 58 months were videotaped during parent-child play interactions and then interviewed about w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 77 publications
0
26
2
Order By: Relevance
“…The results that emerged from the DAOS highlighted that in our sample the abilities to activate a bodily dialogue made up of gestures, sounds and looks (Body scale), to facilitate the child’s actions without overlapping him/her (Autonomy scale) and to understand the mental states of the child (Understanding the Child’s Mental States scale) seemed particularly deficient in most fathers. The result of a very high percentage (80%) of fathers lacking in their ability to become attuned is not in line with the results obtained in our previous study [ 19 ]. This paper stated that 48% fathers and mothers of children with ASD were lacking in parental attunement during play interactions and showed that parents who were more able to accept their child’s diagnosis and to be insightful were more likely to also become attuned with their children diagnosed with ASD [ 19 ].…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…The results that emerged from the DAOS highlighted that in our sample the abilities to activate a bodily dialogue made up of gestures, sounds and looks (Body scale), to facilitate the child’s actions without overlapping him/her (Autonomy scale) and to understand the mental states of the child (Understanding the Child’s Mental States scale) seemed particularly deficient in most fathers. The result of a very high percentage (80%) of fathers lacking in their ability to become attuned is not in line with the results obtained in our previous study [ 19 ]. This paper stated that 48% fathers and mothers of children with ASD were lacking in parental attunement during play interactions and showed that parents who were more able to accept their child’s diagnosis and to be insightful were more likely to also become attuned with their children diagnosed with ASD [ 19 ].…”
Section: Discussioncontrasting
confidence: 89%
“…The Dyadic Attunement Observation Schedule (DAOS) [ 19 ] is an observational measure of parent–child interactions during play. It consists of eight scales that make up a final score of parental attunement: (1) Joint Attention, (2) Body, (3) Interaction, (4) Space Sharing, (5) Play Sharing, (6) Autonomy, (7) Emotional Regulation, (8) Understanding a Child’s Mental States.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations